(untitled) (Asian Journal of Social Science Studies, 2024)
This study investigates the quality of life (QoL) of long-term services and supports (LTSS) recipients and their caregivers in Chengdu, following the implementation of China’s long-term care insurance (LTCI) system. The research utilized three ICEpop CAPability (ICECAP) instruments to evaluate the QoL of both groups and explored the association between the caregivers’ QoL and that of the recipients. A total of 464 LTSS recipients and their caregivers were surveyed, yielding a response rate of 92.8%. Key findings indicated that physical and psychological health were the strongest predictors of higher QoL for both male and female LTSS recipients. Female recipients receiving home care experienced lower QoL, while for males, living with family or supporters was a significant predictor of QoL. Caregivers’ QoL was associated with higher salary, lower education, and better health status, and it was also found to be positively linked to the QoL of LTSS recipients. The study concludes with recommendations for policymakers to consider gender-specific LTSS delivery and to increase salaries for caregivers as a means to improve QoL.